The bone and sinew of the land : America's forgotten black pioneers & the struggle for equality - Cox, Anna-Lisa (New York : PublicAffairs, 2018)
"The American frontier is one of our most cherished and enduring national images. We think of the early settlers who tamed the wilderness and built the bones of our great country as courageous, independent--and white. In this groundbreaking work of deep historical research, Anna-Lisa Cox shows that this history simply isn't accurate. In fact, she has found a stunning number of black settlements on the frontier--in the thousands. Though forgotten today, these homesteads were a matter of national importance at the time; their mere existence challenged rationalizations for slavery and pushed the question toward a crisis--one that was not resolved until the eruption of the Civil War. Blending meticulous detail with lively storytelling, Cox brings historical recognition to the brave people who managed not just to secure their freedom but begin a battle that is still going on today--a battle for equality."--Provided by publisher.
"Life, liberty" -- Interlude -- "The pursuit of happiness" -- "And secure the blessings of liberty." -- "To secure these rights, governments are instituted among men, deriving their just powers from the consent of the governed." -- "Burnt our towns, and destroyed the lives of our people." -- "The right of the people peaceably to assemble." -- "For taking away our charters, abolishing our most valuable laws, and altering fundamentally the forms of our governments" -- "A history of repeated injuries and usurpations." -- Conclusion.
Includes bibliographical references (pages 211-262) and index.
HB
Keywords: African Americans -- Northwest, Old -- History; African Americans -- Indiana -- History -- 19th century; African Americans -- Ohio -- History -- 19th century; Frontier and pioneer life -- Northwest, Old; Frontier and pioneer life -- Indiana; Frontier and pioneer life -- Ohio; African Americans -- Social conditions -- Northwest, Old; Northwest, Old -- History -- 1775-1865.; Northwest, Old -- Race relations